2010
DOI: 10.1063/1.3294642
|View full text |Cite
|
Sign up to set email alerts
|

Impedance spectroscopy as a probe for the degradation of organic light-emitting diodes

Abstract: Nonradiative recombination centers and electrical aging of organic light-emitting diodes: Direct connection between accumulation of trapped charge and luminance loss

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
111
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(118 citation statements)
references
References 29 publications
7
111
0
Order By: Relevance
“…This means that all the organic compounds under investigation reduce more slowly than they oxidise. This result corresponds to a known fact that hole mobility in organic solid films is in most cases much higher than electron mobility [25,26]. Finally, the compounds used as host materials were found to be oxidised and reduced very slowly and irreversibly.…”
Section: Figure 12mentioning
confidence: 67%
“…This means that all the organic compounds under investigation reduce more slowly than they oxidise. This result corresponds to a known fact that hole mobility in organic solid films is in most cases much higher than electron mobility [25,26]. Finally, the compounds used as host materials were found to be oxidised and reduced very slowly and irreversibly.…”
Section: Figure 12mentioning
confidence: 67%
“…For example, in [3] the usage of impedance spectroscopy is described; in [4] an approach using the forward voltage of the OLED is shown. These methods are all anticipated for analog driving and compensating the degradation of current efficiency.…”
Section: Acquisition Of Agingmentioning
confidence: 99%
“…Nevertheless, degradation mechanisms occur and display through a modification of the emission color and/or a reduction of the driving current and the luminance. The effect of aging leads to a progressive increase in impedance during the operation of OLEDs and in order to maintain a constant current, the bias polarization has to be raised more and more [13]. However, it was observed that half lifetime (the time for which the decrease in luminance is 50% from the initial value) and the initial decay are closely related to the amount of non-emissive triplets in emissive layer [9,10].…”
Section: Introductionmentioning
confidence: 97%